Modelo de viento ajustado a un modelo de generación de olas para el pronóstico de oleaje durante huracanes - Lizano Rodríguez, Omar Gerardo (1990)
The characteristics of three forecasting numerical models were studied in order to compare the effects produced in their coupling to a wave generation model. The difference in wave heights produced by the wave generation model were in response to the different wind profiles an its magnitude around the hurricane eye. A new wind model was adapted to the wave generation model to produce better fittness in height and wave energy spectrum using observed data during the hurricane Camille in 1969 in its crossing iver Gulf of Mexico.